2018
DOI: 10.1017/s1368980018001854
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein and changes in markers of cardiometabolic health across 20 years of follow-up in middle-aged Americans

Abstract: Objective: Dietary protein plays a role in counteracting age-related muscle loss. However, limited long-term data exist on protein intake and markers of cardiometabolic health, which tend to deteriorate with age. Design: Prospective cohort study. Food frequency questionnaire-derived protein intake (g/d) and cardiometabolic markers were assessed up to five times across 20 years. Markers included systolic (SBP) and diastolic blood pressures (DBP), circulating lipids (total, HDL, LDL cholesterol; triglycerides)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 64 publications
3
32
1
Order By: Relevance
“…Investigations in populations with higher percentages of protein from plants are merited. Total protein amounts remain nevertheless relevant in aging populations even in the absence of consistently discernible effects on inflammation specifically, owing to potentially favorable associations of higher protein intake with cardiometabolic health (67) and physical function (8, 10, 11). It has been demonstrated that too little protein (e.g., half the RDA compared with the RDA) can have deleterious effects on immune function, lean mass, and muscle function in older women (9).…”
Section: Discussionmentioning
confidence: 99%
“…Investigations in populations with higher percentages of protein from plants are merited. Total protein amounts remain nevertheless relevant in aging populations even in the absence of consistently discernible effects on inflammation specifically, owing to potentially favorable associations of higher protein intake with cardiometabolic health (67) and physical function (8, 10, 11). It has been demonstrated that too little protein (e.g., half the RDA compared with the RDA) can have deleterious effects on immune function, lean mass, and muscle function in older women (9).…”
Section: Discussionmentioning
confidence: 99%
“…Results from interventional studies have also demonstrated that plant protein supplementation results in more favorable serum concentrations of high-density lipoprotein cholesterol (HDL-C), TC, triglycerides (TG), LDL-C, and non-HDL-C compared with animal protein [ 15 , 16 ]. In contrast, other observational studies have found no significant associations between animal or plant protein intake and lipid profiles [ 17 , 18 ]. In addition, available data for the associations between dietary animal and plant protein intake and glucose homeostasis biomarkers [ 17 , 19 ], low-grade inflammatory biomarkers [ 20 , 21 ], and uric acid [ 20 , 22 ] also have heterogeneous findings.…”
Section: Introductionmentioning
confidence: 86%
“…In contrast, other observational studies have found no significant associations between animal or plant protein intake and lipid profiles [ 17 , 18 ]. In addition, available data for the associations between dietary animal and plant protein intake and glucose homeostasis biomarkers [ 17 , 19 ], low-grade inflammatory biomarkers [ 20 , 21 ], and uric acid [ 20 , 22 ] also have heterogeneous findings. Research suggests that the inconsistency may be partially driven by the differential background dietary patterns of study participants [ 23 ].…”
Section: Introductionmentioning
confidence: 86%
“…In some experimental studies, the animal protein ingestion raised serum cholesterol level, but it was not consistent in other studies. Some ecologic studies suggested a positive association between animal protein intake and increased risk of CHD, but the prospective data on this association are not definite [3,8,19,90].…”
Section: Dietary Protein Intake and Cvdmentioning
confidence: 97%